Ambient Air Levels of Aromatic Organic Compounds in the Urban Area of Algiers, Algeria - Kerchich, Yacine; Kerbachi, Rabah; Khatraoui, Hicham (Asian Journal of Chemistry, 2010)
The sampling by "Radiello" diffusion sampler of volatils organic compounds in the ambient air of Algiers reveals the presence of BTEX in all 71 sites sampling chosen. Three representative types of sites were chosen for sample collection at roadside, urban background and semi-rural areas. The samples were taken in two seasons (winter and summer). The following monocyclic aromatic hydrocarbons were found: benzene, toluene, ethylbenzene and (o-,m-,p-)xylene, also referred to as BTEX. Near the road traffic, benzene and toluene mean concentrations were 1.94 and 4.57 μg/m3, respectively, with benzene concentration values higher than 18.29 μg/m3 observed. At the urban site, the average benzene concentration don't exceeds the European regulatory limit of 10 μg/m3 while the compositional ratios of toluene to benzene and (o-,m-,p- )xylene to ethylbenzene are within the typical range of values observed in urban atmospheres worldwide. The seasonal variation indicates a decrease in concentration during summer due of the conditions that favour the depletion of VOC by photochemical degradation. It was found that Algiers source of pollution by aromatic hydrocarbons is related to car traffic emissions.